E-WOM Referral: A New Factor to Influence Your Customer To Purchase - Angela Novianti Gea; Viany Utami Tjhin (LPPM STIKOM Tunas Bangsa, 2023)
Instagram has been the place to exchange information for years. Now businesses can work with influencers to influence their followers to try their endorsement products by using eWOM referral. Every post that talks about a product/service is called eWOM, whether it is out of free will or paid, and a referral means to refer someone else to purchase something. This research will examine factors that can significantly influence purchase intention. A questionnaire will be given to determine the tendencies and calculate using SEM-PLS. The result shows that purchase intention is significantly influenced by information quality and eWOM referral.